Development and Validation of a Semi-Quantitative Food Frequency Questionnaire to Assess Dietary Intake of Turkish School-Aged Children - Güneş Fatma Esra; Elmacıoğiu Funda; Aktaç Şule; Sağlam Duygu (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to develop and validate a food frequency questionnaire (FFQ) on the dietary intake of Turkish school-aged children. Fifty randomly selected students aged 7–12 from urban areas of Istanbul were included in this study. An FFQ, containing a list of 138 frequently consumed foods was developed. Dietary records (DRs) including three days, and FFQs were collected during autumn and spring. Daily consumption of each food group was assessed and the nutrient compositions of diet were calculated. The Pearson correlation coefficient, weighted kappa, the Bland-Altman scatter plots between averages of the reported (FFQ) and the references method (DR) were used as validity coefficient.